Recent Progress on BaTiO3-Based Piezoelectric Ceramics for Actuator Applications - Gao, Jinghui; Xue, Dezhen; Liu, Wenfeng; Zhou, Chao; Ren, Xiaobing (Actuators, 2017)
Due to issues with Pb toxicity, there is an urgent need for high performance Pb-free alternatives to Pb-based piezoelectric ceramics. Although pure BaTiO3 material exhibits fairly low piezoelectric coefficients, further designing of such a material system greatly enhances the piezoelectric response by means of domain engineering, defects engineering, as well as phase boundary engineering. Especially after the discovery of a Ba(Zr0.2Ti0.8)O3–x(Ba0.7Ca0.3)TiO3 system with extraordinarily high piezoelectric properties (d33 > 600 pC/N), BaTiO3-based piezoelectric ceramics are considered as one of the promising Pb-free substitutes. In the present contribution, we summarize the idea of designing high property BaTiO3 piezoceramic through domain engineering, defect-doping, as well as morphotropic phase boundary (MPB). In spite of its drawback of low Curie temperature, BaTiO3-based piezoelectric materials can be considered as an excellent model system for exploring the physics of highly piezoelectric materials. The relevant material design strategy in BaTiO3-based materials can provide guidelines for the next generation of Pb-free materials with even better piezoelectric properties that can be anticipated in the near future.